Internet adoption and usage patterns among Students in selected South African Universities - Kassangoye, Wilfred; ., Robert Rugimbana (Journal of Economics and Behavioral Studies, 2013)
This study examines the case of student adoption and usage patterns of the Internet as an innovation in delivering important services that include financial services. The quantitative approach employed in this study utilizes an extended version of Rogers’ model of perceived innovation attributes. Consistent with previous studies, the perceived innovation attributes were found to be important determinants of students’ adoption decisions. However, two dimensions, namely relative advantage and perceived usefulness were found to influence this consumer groups’ adoption decisions more prominently, thus highlighting the complex nature of the innovation and adoption decisions for Internet services users.